Microplastics in beach sediments, seawater, and common fish in tourist destinations - M. Go; A. Ybanez; A. Ilano; F. Cababat; L. De La Calzada (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The global concern over microplastic pollution has been on the rise, primarily due to its detrimental effects on marine ecosystems and the potential health risks it poses to humans. Tourism activities are the main sources of plastic waste that deteriorates into microplastics. This study monitors microplastic contamination in marine environments at tourist destinations and suggests policies and initiatives that encourage tourism operators, locals, and tourists to adopt practices that reduce microplastic pollution. This endeavor is in line with the journal''''''''s objective to oversee the environmental consequences and advocate for improved environmental management strategies. This study aims to quantify microplastics in beach sediments, seawater, and the gastrointestinal tract and muscles of three fish species, Selar crumenophthalmus, Auxis thazard, and Sardina pilchardus, which are commonly found in the municipalities of Moalboal and Badian, tourist destinations in Southern Cebu Province, Philippines.METHODS: This study followed the approved procedures outlined in prior studies for gathering, handling, and examining microplastics found in sediment, seawater, and fish tissue samples. Sediment and seawater were collected from four sampling points at each study site using sterilized bottle containers. Sediment samples underwent oven-drying, passed through a 5-millimeter mesh, underwent density separation with a saturated salt solution, and were then filtered with filter paper. For seawater, the bottle grab method was utilized for sampling, followed by gravity filtration performed in triplicate to ensure thorough extraction of microplastics. The selection of fish species was determined by their common presence in nearby markets. Samples of gastrointestinal tract and muscle tissues were meticulously processed, treated with chemicals, and digested in order to aid in the isolation of microplastics. The quantification of microplastics was conducted under a stereomicroscope.FINDINGS Moalboal exhibited higher average microplastic counts in sediments (0.12 items per gram) and seawater (0.06 items per gram) than Badian, which had 0.08 items per gram in sediments and 0.04 items per gram in seawater. There was no significant difference in the microplastic levels found in sediments and seawater between the two towns, as indicated by a p-value greater than 0.05. Similarly, there were no significant differences in microplastic abundance in fish between these sites. Significant disparities were noted in the abundance of microplastics across distinct fish species and anatomical segments. Auxis thazard showed significantly the highest microplastic particles (0.33 ± 0.10 in muscles; 0.077 ± 0.04 in the gastrointestinal tract) than other species. The microplastic abundance between Selar crumenophthalmus (0.20 ± 0.09; 0.055 ± 0.03), and Sardinella pilchardus (0.16 ± 0.03; 0.050 ± 0.04) did not significantly differ. In each fish sample, the presence of microplastics was notably more pronounced in the gastrointestinal tract than in the muscle tissue, demonstrating a statistically significant difference at a significance level of p